1967
DOI: 10.1002/jez.1401660110
|View full text |Cite
|
Sign up to set email alerts
|

The relation between the caliber of the axon and the trophic activity of nerves in limb regeneration

Abstract: Previous work from this laboratory demonstrated a relation between ability to regenerate a limb and number of nerve fibers available per unit area of amputation wound. Animals with fewer fibers than the newt, Triturus, (for example, Rana, Anolis, and Mus) do not regrow the limb. An exception appeared in Xenopus whose limb is sparsely innervated and yet which regenerates. The present work demonstrates that the nerve fibers of Xenopus make up in individual size what they lack in number. When the average cross-se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

1969
1969
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…Again, work on this aspect of regeneration has focused on the caudal end of the regenerating tail [9], [12], [15], [47], thus little is known about the role of bioelectrical signals originating in tissue that is not near the amputation plane. Classical studies in salamanders had shown that innervation is crucial to regenerative ability [48], [49], [50]. However, those data had not demonstrated a role for the nervous system in patterning of the regenerate, and were largely consistent with permissive factors allowing the process to go forward.…”
Section: Discussionmentioning
confidence: 99%
“…Again, work on this aspect of regeneration has focused on the caudal end of the regenerating tail [9], [12], [15], [47], thus little is known about the role of bioelectrical signals originating in tissue that is not near the amputation plane. Classical studies in salamanders had shown that innervation is crucial to regenerative ability [48], [49], [50]. However, those data had not demonstrated a role for the nervous system in patterning of the regenerate, and were largely consistent with permissive factors allowing the process to go forward.…”
Section: Discussionmentioning
confidence: 99%
“…It has long been known that innervation is required for limb regeneration (Goss, 1969; Rose, 1948; Singer et al, 1967), and recent molecular evidence has uncovered genes responsible for the acquired nerve-dependence of amphibian limbs (Kumar et al, 2007). Classical work suggested that the CNS indeed carries important aspects of morphogenetic fields (Becker, 1961), but the information content of neutrally-mediated signals remains to be probed in mechanistic detail.…”
Section: Organizational Level and Scale Properties Of Morphogenetimentioning
confidence: 99%
“…Goss (1969) proposed that such type of unidirectional regeneration was possible because the ablation severed the nervous system network, depriving the distal part of the rays of their normal innervation. This convincing interpretation finds roots in the necessity of an adequate nerve supply for regeneration to occur, in fins (Géraudie and Singer, 1977, 1985) as well as in newt limb (Singer et al, 1967; Singer, 1974; Brockes, 1987). Indeed, nerve resection at the level of the pectoral girdle in teleosts (Fundulus) at the time of amputation of the pectoral fin prevents the formation of the blastema.…”
Section: Importance Of the Nervous System For The Initiation Of Fin Rmentioning
confidence: 99%